(untitled) (Research, Society and Development, 2020)
This study aims to perform the thermal analysis of Japanese rice starch submitted to different milling processes (balls, discs and knives). Starch was extracted with sodium metabisulphite solution (0.2%), crushed, decanted and dried at (50 °C) to constant weight. The thermal properties were analyzed by thermogravimetry and differential exploratory calorimetry techniques. It can be argued that the granules of the Japanese rice native starch are poorly resistant and knife milling made them more susceptible to breakage with prolonged heating. The different milling techniques significantly modified the thermal properties of the Japanese rice starch, since in the thermogravimetry analysis the formulation obtained through the disc mill presented distinction in relation to the mass loss, while for the differential exploratory calorimetry the starch obtained in the process. The milling process with the ball mill presented lower initial gelatinization temperature and higher gelatinization enthalpy.